Transcription enhances AID-mediated cytidine deamination by exposing single-stranded DNA on the nontemplate strand - Ramiro, Almudena R.; Stavropoulos, Pete; Jankovic, Mila; Nussenzweig, Michel C. (Nature immunology, 2003)
Somatic hypermutation and class switch recombination are DNA modification reactions that alter the genes encoding antibodies in B lymphocytes. Both of these distinct reactions require activation-induced deaminase (AID) and transcription. Here we show that in Escherichia coli , as in eukaryotic cells, the mutation frequency is directly proportional to the transcription of target genes. Transcription enhances mutation of the nontemplate DNA strand, which is exposed as single-stranded DNA during the elongation reaction, but not mutation of the template DNA strand, which is protected by E. coli RNA polymerase. Our results establish a direct link between AID and transcription and suggest that the role of transcription in facilitating mutation is to provide AID with access to single-stranded DNA.